2011
DOI: 10.1007/s12272-011-0710-2
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi approach for anti-heat stress prescription compatibility in mice spleen lymphocytes In Vitro

Abstract: Heat stress (HS) may induce immunosuppression as well as inhibit the proliferation of lymphocytes. This study evaluated the effects on immune function of our prescription on splenic lymphocytes under HS as well as its compatibility. The effects of four herbal extracts from Agastache rugosa, Atractylodes lancea, Cortex Phellodendri, and Gypsum Fibrosum on heat treated splenic lymphocytes were investigated and the compatibility of the prescription was also explored by using the Taguchi method. This study reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that the bark of Huang Bai has antidiabetic [ 18 ], anti-heat stress [ 19 ], anti-inflammatory [ 20 ], antimicrobial [ 21 , 22 ], and neuroprotective [ 23 ] effects and that the spike of Xia Ku Cao exhibits antitumor [ 24 , 25 ] and immunosuppressive [ 26 ] activities. Similarly, the rhizome of Zhi Mu possesses antidiabetic, anti-inflammatory, anticoagulatory, antihypertensive, antitumor, antioxidative, antimicrobial, antiviral, antiosteoporosis, anti-skin aging, and neuroprotective [ 27 ] effects; additionally, the fruit of Mai Ya exerts antihyperprolactinemia activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the bark of Huang Bai has antidiabetic [ 18 ], anti-heat stress [ 19 ], anti-inflammatory [ 20 ], antimicrobial [ 21 , 22 ], and neuroprotective [ 23 ] effects and that the spike of Xia Ku Cao exhibits antitumor [ 24 , 25 ] and immunosuppressive [ 26 ] activities. Similarly, the rhizome of Zhi Mu possesses antidiabetic, anti-inflammatory, anticoagulatory, antihypertensive, antitumor, antioxidative, antimicrobial, antiviral, antiosteoporosis, anti-skin aging, and neuroprotective [ 27 ] effects; additionally, the fruit of Mai Ya exerts antihyperprolactinemia activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the effects of these TCM decoctions in vitro enhanced the antioxidant status and reduced lipid peroxidation in heat-stressed intestinal crypt-like epithelial cells (Guo et al, 2011). As well, the effects of these herbal extracts may recover splenic lymphocytes from the immunosuppression induced by heat stress (Zhu et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…According to veterinary research, Cangzhu possessed the ability of anti-heat stress in spleen and intestine ( Xu et al, 2017 ). In addition, the polysaccharide of Cangzhu was shown to have the protective effects on endoplasmic reticulum stress and apoptosis in HS-induced spleen injury ( Zhu et al, 2011 ). Chanxinlian ( Andrographis paniculata ) is a type of herb with a strong bitter taste used to treat sore throats, common cold, and noninfective diarrhea ( Dai et al, 2019 ).…”
Section: Single Chinese Herbs and Associated Extracts Or Monomers Aga...mentioning
confidence: 99%